A boron-containing composite particle and a method for producing the same

CN122916797APending Publication Date: 2026-10-16NAVAL UNIV OF ENG PLA
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611207004.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2026-04-13
Filing Date
2026-08-10
Publication Date
2026-10-16

AI Technical Summary

Technical Problem

但是,各种工艺改性,尤其是镁(Mg)、铝与硼混合或者复合后,虽然直接或者间接提高了硼的反应完全性,提高了能量释放效果,但是其内部存在大量的界面和间隙,硼及硼基复合材料的密度下降,导致实际应用的效果不好,制约了硼的应用

Benefits of technology

本发明的含硼复合粒子具有能量高、安全性优良的特点,燃烧热能够达到32kJ/g以上;应用到造型粉中,生产压装炸药,药柱密度能够达到理论密度的92%以上,机械感度低于40%。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122916797A_ABST
    Figure CN122916797A_ABST
Patent Text Reader

Abstract

The present application relates to a kind of boron-containing composite particles and its preparation method, the boron-containing composite particles are boron-magnesium-aluminum composite particles, improve the combustion performance of boron are modified.The specific process includes preparation boron-magnesium-aluminum composite particles, hydrogen storage and liquid phase impregnation three steps.Among them, hydrogen storage is washed by ammonia, boron-magnesium-aluminum composite particles are placed into rotary furnace, hydrogen storage is realized by the reaction of hydrogen and magnesium, this step is carried out in rotary furnace, and rotary furnace is mainly composed of spherical pot, plug cover, heating jacket and vibration table;The filling liquid used in liquid phase impregnation is composed of perfluorohexane, perfluorooctyl polyoxyethylene ether and vinylidene fluoride-trifluorochloroethylene copolymer.The boron-containing composite particles of the present application have the characteristics of high energy and excellent safety, and the combustion heat can reach more than 30 kJ / g;When applied to molding powder, production press-loaded explosive, the density of the grain can reach more than 92% of the theoretical density, and the mechanical sensitivity is less than 40%.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of explosives materials, and specifically to a boron-containing composite particle and its preparation method, which can be used as a high-energy combustion agent. Background Technology

[0002] The most commonly used fuels in explosives are aluminum (Al) and boron (B). Compared to Al, B has a higher calorific value when completely burned, but B powder is difficult to burn completely. B itself has a high melting and boiling point, and its surface has an initial oxide layer—boron oxide (B₂O₃). Boron oxide has a low melting point and a high boiling point, making it difficult to evaporate. During combustion, it melts into a liquid film that coats the surface of B particles, preventing B from contacting external oxygen and making ignition difficult. Therefore, improving the complete combustion of B has always been a key research direction for researchers in the field of energetic materials, and achieving efficient and complete combustion of B through combustion-enhancing modification technology is a crucial and highly valuable technical path in this research direction.

[0003] According to literature analysis, scholars both domestically and internationally have employed various methods to improve the reactivity of boron, including metal activation and fluorinated binder coating. Evaluating the application of metallic fuels in explosives requires attention not only to their mass combustion capacity but also to their volumetric combustion capacity, i.e., the energy density of the explosive. However, while various process modifications, especially the mixing or composite of magnesium (Mg) and aluminum with boron, directly or indirectly improve the reactivity of boron and enhance energy release, the presence of numerous interfaces and gaps within these processes leads to a decrease in the density of boron and boron-based composites, resulting in poor practical application and limiting the application of boron. Summary of the Invention

[0004] To address the aforementioned problems, this invention provides a boron-containing composite particle and its preparation method. The main method involves modifying a boron-magnesium-aluminum metal composite. First, the boron-magnesium-aluminum metal composite is hydrogenated, where a large amount of hydrogen comes into contact with magnesium to form solid hydrogen, which is then filled into the composite. Next, a filling liquid is added to fill the gaps, and finally, a coating material is used for coating and shaping.

[0005] The design concept of this invention is as follows: Based on extensive basic and experimental research, this invention discovers that mixing or combining magnesium, aluminum, and boron significantly improves the completeness of boron's reaction and significantly increases the heat of combustion per unit mass. However, when applied to actual propellant loading, while the mass energy is increased, the volumetric energy decreases. Analysis reveals that the actual density of the composite is far lower than the theoretical density, especially after mixing boron, magnesium, and aluminum (MgA), where the actual density in the propellant loading is only about 80% of the theoretical density, severely impacting the application of MgA materials. The low actual density of MgA materials is due to the large number of voids within them. Significant technical optimization can be achieved if a material meets the following characteristics: First, the material must possess excellent permeability, capable of overcoming mass transfer barriers on the surface of complex-shaped particles and effectively filling the internal gaps of the MgA composite particles, thereby increasing the propellant density; second, if the filling material can participate in the exothermic combustion reaction of the MgA system, the energy density of the system can be further improved; third, the filling process must increase particle mass while minimizing volume gain to ensure an increase in propellant density. Theoretical analysis and experimental studies have shown that boron readily forms a boron oxide (B2O3) surface layer during combustion. This layer hinders the contact between boron and the oxidant, inhibiting the continued combustion reaction. The introduction of fluorine and hydrogen can significantly improve the combustion efficiency of boron by disrupting or modifying the boron oxide layer. Based on this, this invention fills the internal pores of boron-magnesium-aluminum composite particles with fluoride and utilizes the magnesium-hydrogen reaction to store hydrogen on the magnesium surface within the pores, thereby optimizing combustion performance and energy characteristics.

[0006] To achieve this objective, the concept of this invention is twofold: First, to design a fluorine-containing material to fill the interior of the particles. The challenge lies in the complex structure of the composite particles, requiring the fluorine-containing material to overcome external barriers and be able to store hydrogen within the internal pores. Second, to store hydrogen on the surface of the metal particles. The challenge is that, unlike conventional magnesium surface storage technology, boron-magnesium-aluminum composite particles adsorb moisture from the air during preparation, which affects magnesium's hydrogen adsorption. Moisture (especially water vapor in the air) has a severely negative impact on magnesium's hydrogen storage performance, posing a major challenge to its practical application. This impact is not merely interference, but destructive. Magnesium-aluminum alloy powders pose a risk of combustion and explosion during drying; direct open heating in an oven is strictly prohibited. All operations must be carried out under an inert atmosphere or vacuum. Furthermore, conventional dehydration methods such as vacuum heating, inert gas heating, molecular sieves, and freeze drying can only remove free water and are unsuitable for removing the water film on the metal surface inside the boron-magnesium-aluminum particles. The concept of this invention is mainly implemented in the following four steps: The first step is to prepare boron-magnesium-aluminum composite particles. The technology for preparing boron-magnesium-aluminum particles is very mature. Energy testing shows that a significant hydrogen storage effect can only be achieved when the magnesium content is not less than 5%.

[0007] The second step is hydrogen solidification and energy storage. Pressurized hydrogen solidification is the core technology of this invention. A dynamic heating hydrogen solidification technology was designed, in which boron-magnesium-aluminum particles are placed in a rotary furnace. After multiple ammonia scrubbing processes, high-pressure ammonia gas (0.2 MPa–0.4 MPa) is introduced, and a vibration table is activated at a frequency of 10 Hz–20 Hz. Simultaneously, the temperature is heated to 40°C–50°C, and the pressure and temperature are maintained during vibration for at least 15 minutes. After multiple hydrogen scrubbing processes, high-pressure hydrogen gas (not less than 1.0 MPa) is introduced, and rotation is started at a speed of at least 1 r / min. Simultaneously, the temperature is heated to 100°C–120°C, and the pressure and temperature are maintained during rotation for at least 1 hour. The pressure is then reduced to remove the hydrogen, yielding solid hydrogen particles. The core objective of this step is to utilize the chemical reaction between high-pressure hydrogen gas and magnesium in the composite particles to achieve high-capacity solid-state hydrogen storage on the surface of magnesium within the composite particles. This hydrogen storage method is one of the most promising high-capacity solid-state hydrogen storage technologies currently available. However, the key challenge lies in solving the water film problem and preventing hydrogen storage on the outer surface. Rotation is used to reduce external hydrogen storage, as excessive external hydrogen storage increases the probability of hydrogen contact with explosives during use, reducing safety. High-pressure ammonia is used to remove water molecules from the surface of composite particles to prevent surface poisoning and structural damage. Vibration is used to disrupt the energy balance between water and magnesium and promote the reaction between ammonia and water.

[0008] The third step is liquid-phase impregnation. A filling liquid composed of perfluorohexane, perfluorooctyl polyoxyethylene ether, and vinylidene fluoride-trifluorochloroethylene copolymer was designed. Through capillary action, the filling liquid fills the interior of the hydrogen-fixing particles. The filling liquid is added to a rotary furnace under vacuum using a peristaltic pump. After addition, the vacuum is removed, and the particles are soaked for at least 30 minutes. The filling liquid is then removed by filtration, followed by vacuum drying to obtain boron-containing composite particles. Perfluorohexane has extremely low surface tension, allowing it to easily penetrate into tiny gaps. However, perfluorohexane has strong hydrophobicity. The high-pressure ammonia gas used in the previous step can only remove water molecules from the surface of the composite particles to prevent surface poisoning and structural damage. However, water molecules will still react with ammonia gas (NH3 + H2O = NH3·H2O) to generate ammonia water. The trace amounts of ammonia water in the gaps will hinder the filling of perfluorohexane. This invention uses perfluorooctyl polyoxyethylene ether to improve the filling effect of perfluorohexane. The fluorocarbon chain structure of perfluorooctyl polyoxyethylene ether, similar to a "fluorine-fluorine affinity," can effectively adsorb at the interface of perfluorohexane droplets, stably dispersing them in water. However, perfluorohexane is highly volatile, leading to back-precipitation after packing. This problem can be solved by using vinylidene fluoride-chlorotrifluoroethylene copolymer. When perfluorohexane volatilizes, the vinylidene fluoride-chlorotrifluoroethylene copolymer dissolved in the perfluorohexane precipitates out, achieving a sealing effect.

[0009] Furthermore, the filling liquid is composed of perfluorohexane, perfluorooctyl polyoxyethylene ether, and vinylidene fluoride-trifluorochloroethylene copolymer, wherein 100 parts of perfluorohexane, 5-12 parts of vinylidene fluoride-trifluorochloroethylene copolymer, and 0.5-2 parts of perfluorooctyl polyoxyethylene ether.

[0010] Furthermore, this invention designs a rotary furnace, which consists of a spherical pot 1, a plug 2, a heating jacket 3, and a vibration table 4. The spherical pot 1 and the plug 2 are connected by a flange and have a pressure resistance of not less than 3MPa. The plug 2 has a gas port 5 and a liquid port 6. The gas port 5 is used to introduce ammonia or hydrogen and to create a vacuum, while the liquid port 6 is used to inject filling liquid into the pot. The heating jacket 3 can be supplied with hot water through a water inlet 7 and a water outlet 8 to heat and keep the spherical pot 1 warm. The spherical pot 1 and the heating jacket 3 are connected by a ring track 9. The heating jacket is placed on the vibration table 4, which has a vibration frequency of 10Hz to 20Hz and a maximum amplitude of not less than 2mm. The heating jacket 3 has a rotating shaft in the middle, which drives the spherical pot 1 to rotate under external power. The rotation axis makes an angle of 40° to 50° with the horizontal plane. After preparation, the product needs to be stored under vacuum conditions, or directly used to prepare molding powder, or used as other energetic particles. The molding powder preparation technology is relatively mature, and the specific operation is as follows: Dissolve fluororubber in ethyl acetate, add an oxidant, mix evenly, and then add filler particles; continue mixing under open conditions to allow the solvent to evaporate until the slurry becomes a thick paste; prepare boron-containing composite particles by sieving or granulating with a granulator.

[0011] This invention is only applicable to amorphous boron-magnesium-based or boron-magnesium-aluminum particles, and is not applicable to crystalline boron or boron-aluminum metal compositions that do not contain magnesium.

[0012] The beneficial effects of this invention are as follows: The boron-containing composite particles of this invention have the characteristics of high energy and excellent safety, and the heat of combustion can reach more than 32kJ / g. When applied to molding powder to produce compressed explosives, the density of the explosive charge can reach more than 92% of the theoretical density, and the mechanical sensitivity is less than 40%.

[0013] This invention can significantly improve the density of mixed explosive charge containing boron-added composite particles. Under the same proportion, the relative density of the charge increases from 89.2% to 96.1%, the heat of combustion increases from 28.69 kJ / g to 32.64 kJ / g, and the mechanical sensitivity decreases from 68% to 32%. The pressurized hydrogen fixation and liquid phase impregnation effects can significantly improve the energy, which has significant technical advantages.

[0014] The present invention has significant technical advantages after using a filler liquid. Without adding perfluorooctyl polyoxyethylene ether and without using a filler liquid, the energy is reduced and the safety is significantly decreased.

[0015] The hydrogen storage method used in this invention has significant technical advantages. Without this invention or by simply using hydrogen to store hydrogen on the magnesium surface, the energy cannot be increased. The main reason is that the water does not achieve a significant hydrogen storage effect, and the fluorine-containing materials in the subsequent process do not catalyze the release of boron, resulting in a significant decrease in energy. Attached Figure Description

[0016] Figure 1 This is a schematic diagram of the rotary furnace structure; The components represented by the numbers in the diagram are: 1-spherical pot, 2-plug, 3-heating jacket, 4-vibrating table, 5-air inlet, 6-liquid inlet, 7-water inlet, 8-water outlet, 9-circular track.

[0017] Figure 2 This is an EDS scan of the boron-containing composite particles prepared in Example 1.

[0018] The present invention will now be described in detail with reference to the embodiments. Detailed Implementation

[0019] The following examples are provided to help you better understand the present invention, but they are not intended to limit the invention. Example

[0020] This embodiment, by weight, consists of the following raw materials: 25g of amorphous boron powder (500μm particle size); 60g of spherical aluminum powder (13μm particle size); and 15g of magnesium powder (200μm particle size). The filling solution is composed of perfluorohexane, perfluorooctyl polyoxyethylene ether, and vinylidene fluoride-chlorotrifluoroethylene copolymer, wherein 500g of perfluorohexane, 45g of vinylidene fluoride-chlorotrifluoroethylene copolymer, and 8g of perfluorooctyl polyoxyethylene ether. Perfluorohexane, perfluorooctyl polyoxyethylene ether, and vinylidene fluoride-chlorotrifluoroethylene copolymer are added to a covered glass and stirred until the vinylidene fluoride-chlorotrifluoroethylene copolymer is completely dissolved to prepare the filling solution.

[0021] Preparation process of boron-containing composite particles: (1) Preparation of boron-magnesium-aluminum composite particles: Magnesium powder, aluminum powder and n-heptane were added to a steel ball mill jar by ball milling process and magnesium-aluminum alloy powder was prepared at 400 r / min; boron powder was added and n-heptane was added. After ball milling, vacuum drying was performed to obtain boron-magnesium-aluminum composite particles.

[0022] (2) Hydrogen storage: The boron-magnesium-aluminum composite particles prepared in the previous step are placed in a rotary furnace, heated, vacuumed and degassed, and after maintaining the pressure less than 100 Pa, ammonia is introduced, and then vacuumed again. This process is repeated more than 3 times. High-pressure ammonia is introduced at a pressure of 0.4 MPa, vibration is started at a frequency of 10 Hz, and the temperature is heated to 40℃. The pressure and temperature are maintained and the rotation is carried out for 30 minutes. The pressure is reduced and vacuumed to remove ammonia. After maintaining the pressure less than 100 Pa, hydrogen is introduced, and then vacuumed again. This process is repeated 3 times. High-pressure hydrogen is introduced at a pressure of 1.0 MPa, rotation is started at a speed of not less than 1 r / min, and the temperature is heated to 100℃. The pressure and temperature are maintained and the rotation is carried out for 2.5 h. The hydrogen is removed by depressurization to obtain hydrogen-solidified particles. (3) Liquid phase impregnation: The filling liquid is added to the rotary furnace in a vacuum environment. After the filling liquid is added, the vacuum is removed, the filling liquid is soaked for 30 minutes, filtered to remove the filling liquid, and vacuum dried to obtain boron-containing composite particles.

[0023] In the above preparation process, the solid hydrogen storage and liquid phase impregnation processes are carried out in a rotary furnace, as shown in the attached diagram. Figure 1 As shown. Ammonia and hydrogen are introduced through the gas port (5) and a vacuum is drawn. The liquid port (6) is used to inject filling liquid into the pot. Hot water is introduced into the heating jacket (3) through the water inlet (7) and water outlet (8) to heat and keep the spherical pot (1) warm.

[0024] Preparation and pressing of molding powder: (1) Dissolve 5g of fluororubber in ethyl acetate, add 60g of HMX, mix, and then add 35g of boron-containing composite particles; (2) Continue mixing under open conditions to evaporate the solvent at a temperature of 45°–60°C until the slurry becomes a thick paste; (3) Explosive molding powder is obtained by sieving and granulation; (4) Preparation of explosive charge: A compression molding test was conducted on a material testing machine using the compression method, with a loading speed of 0.5 mm / min. The explosive molding powder was weighed and filled into a mold with an inner diameter of 16 mm. After being kept at 60℃ for 2 h, the charge was pressed and molded at a pressure of 140 MPa. After holding the pressure for 30 s, the pressure was released and the charge was demolded to obtain explosive charge. Each charge weighed 5 g ± 0.5 g and had a diameter of 16 mm. Example

[0025] This embodiment, by weight, consists of the following raw materials: 25g of amorphous boron powder (500μm particle size); 60g of spherical aluminum powder (13μm particle size); and 15g of magnesium powder (200μm particle size). The filling solution is composed of perfluorohexane, perfluorooctyl polyoxyethylene ether, and vinylidene fluoride-chlorotrifluoroethylene copolymer, wherein 500g of perfluorohexane, 25g of vinylidene fluoride-chlorotrifluoroethylene copolymer, and 2.5g of perfluorooctyl polyoxyethylene ether. Perfluorohexane, perfluorooctyl polyoxyethylene ether, and vinylidene fluoride-chlorotrifluoroethylene copolymer are added to a covered glass and stirred until the vinylidene fluoride-chlorotrifluoroethylene copolymer is completely dissolved to prepare the filling solution.

[0026] Preparation process of boron-containing composite particles: (1) Preparation of boron-magnesium-aluminum composite particles: Same as in Example 1; (2) Hydrogen storage: The boron-magnesium-aluminum composite particles prepared in the previous step are placed in a rotary furnace, heated, and degassed under vacuum. After maintaining the pressure below 100 Pa, ammonia is introduced, and then vacuum is evacuated again. This process is repeated more than 3 times. High-pressure ammonia is introduced at a pressure of 0.2 MPa, vibration is started at a frequency of 20 Hz, and the temperature is heated to 50°C. After maintaining the pressure and temperature, the vibration is maintained for 15 minutes. The pressure is reduced and vacuum is evacuated to remove ammonia. After maintaining the pressure below 100 Pa, hydrogen is introduced, and then vacuum is evacuated again. This process is repeated 3 times. High-pressure hydrogen is introduced at a pressure of 1.0 MPa, rotation is started at a speed of not less than 1 r / min, and the temperature is heated to 120°C. After maintaining the pressure and temperature, the rotation is maintained for 1 hour. The hydrogen is removed by reducing the pressure to obtain hydrogen-solidified particles. (3) Liquid phase impregnation: The filling liquid is added sequentially under vacuum. After adding, the vacuum is removed, the mixture is soaked for 15 minutes, filtered to remove the filling liquid, and then vacuum dried to obtain boron-containing composite particles.

[0027] In the above preparation process, the solid hydrogen storage and liquid phase impregnation processes are carried out in a rotary furnace, as shown in the attached diagram. Figure 1 As shown. Ammonia and hydrogen are introduced through the gas port (5) and a vacuum is drawn. The liquid port (6) is used to inject filling liquid into the pot. Hot water is introduced into the heating jacket (3) through the water inlet (7) and water outlet (8) to heat and keep the spherical pot (1) warm.

[0028] The preparation and pressing process of the molding powder in this embodiment is the same as in Embodiment 1. Example

[0029] This embodiment, by weight, comprises the following raw materials: 25g of amorphous boron powder (500μm particle size); 60g of spherical aluminum powder (13μm particle size); and 15g of magnesium powder (200μm particle size). The filling solution consists of perfluorohexane, perfluorooctyl polyoxyethylene ether, and vinylidene fluoride-chlorotrifluoroethylene copolymer, wherein 500g of perfluorohexane, 60g of vinylidene fluoride-chlorotrifluoroethylene copolymer, and 10g of perfluorooctyl polyoxyethylene ether. Perfluorohexane, perfluorooctyl polyoxyethylene ether, and vinylidene fluoride-chlorotrifluoroethylene copolymer are added to a covered glass and stirred until the vinylidene fluoride-chlorotrifluoroethylene copolymer is completely dissolved to prepare the filling solution.

[0030] The preparation process of boron-containing composite particles and the preparation and pressing process of molding powder in this embodiment are the same as in Embodiment 2.

[0031] Comparative Example 1 The formulation, boron-containing composite particle preparation process, molding powder preparation and pressing are the same as in Example 1, except that solid hydrogen energy storage and liquid phase impregnation are not used.

[0032] Comparative Example 2 The formulation, boron-containing composite particle preparation process, molding powder preparation and pressing were the same as in Example 1, except that the filling liquid was composed entirely of perfluorohexane and vinylidene fluoride-trifluorochloroethylene copolymer, without the addition of perfluorooctyl polyoxyethylene ether.

[0033] Comparative Example 3 The formulation, boron-containing composite particle preparation process, molding powder preparation and pressing are the same as in Example 1, except that ammonia is replaced with hydrogen in the solid hydrogen energy storage process.

[0034] Performance Evaluation (1) Relative density: The test object was an explosive charge. Referring to "Preparation and Performance Study of TATB / HMX Eutectic Explosives" (Journal of Explosives and Pyrotechnics, 2017, 40), the theoretical density of the charge was calculated as ρ0, g / cm³. 3 The actual density of the propellant column, ρ, g / cm³, was tested according to method 401.2 of GJB772A-97 using the water displacement method. 3 Relative density d = ρ / ρ0 × 100%.

[0035] (2) Mechanical sensitivity: The test object is modeling powder, and the friction sensitivity test is carried out by GJB772A-97 method 602.1 explosion probability method.

[0036] (3) Combustion heat test: The test object is boron-containing composite particles, and the method of GJB5891.29-2006 is adopted. The container is a quartz crucible, the oxygen pressure is 2.8MPa, and the distilled water is 2L.

[0037] (4) EDS scan: The test object is a boron-containing composite particle. The elemental composition of a single composite particle is scanned using the energy dispersive spectroscopy (EDS) function of the scanning electron microscope. Implementation effect

[0038] The performance test results of the embodiments and comparative examples of the present invention are shown in the table below: Table 1

[0039] Implementation effect analysis: (1) As seen in Example 1, the present invention achieves the characteristics of high energy and excellent safety of boron-containing composite particles. The heat of combustion can reach more than 32kJ / g, and the actual value is 32.64kJ / g. When applied to molding powder to produce press-loaded explosives, the density of the explosive charge can reach more than 92% of the theoretical density, and the actual value is 96.1%. The mechanical sensitivity is 32%, which is less than 40%.

[0040] (2) Appendix Figure 2 This is the EDS image of Example 1. From left to right, the image shows the TEM image and the distribution of fluorine, magnesium, and aluminum elements in Example 1. As can be seen from the image, the fluorine element in the particles prepared in Example 1 is uniformly distributed without any aggregation.

[0041] (3) Compared with Example 1 and Comparative Example 1, the present invention can significantly improve the density of the mixed explosive charge containing boron-added composite particles. Under the same ratio, the relative density of the charge increases from 89.2% to 96.1%, the heat of combustion increases from 28.69 kJ / g to 32.64 kJ / g, and the mechanical sensitivity decreases from 68% to 32%. The pressurized hydrogen fixation and liquid phase impregnation can significantly improve the energy, which has significant technical advantages.

[0042] (4) Comparing Example 1, Comparative Example 2 and Comparative Example 1, it can be seen that the filling liquid designed in this invention has significant technical advantages. When perfluorooctyl polyoxyethylene ether is not added and the filling liquid is not used, the energy is reduced and the safety is significantly reduced.

[0043] (5) Comparing Example 1 and Comparative Example 3, it can be seen that the hydrogen storage method designed in this invention has significant technical advantages. Without the present invention or by using only hydrogen to store hydrogen on the magnesium surface, the energy cannot be improved. The main reason is that the hydrogen storage effect is not achieved due to the effect of water, and the fluorine-containing materials brought by the subsequent process do not catalyze the release of boron, resulting in a significant decrease in energy.

[0044] The above description provides examples of the preferred embodiments of the present invention. Parts not detailed herein are common knowledge to those skilled in the art. The scope of protection of the present invention is determined by the claims. Any equivalent modifications based on the technical teachings of the present invention are also within the scope of protection of the present invention.

Claims

1. A method for preparing boron-containing composite particles, characterized in that, Includes the following steps: Step 1: Prepare boron-magnesium-aluminum composite particles, wherein the magnesium content in the boron-magnesium-aluminum composite particles is not less than 5%; Step 2, hydrogen storage: In a rotary furnace, the boron-magnesium-aluminum composite particles are first dehydrated, and then hydrogen is stored on the surface of magnesium inside the composite particles through a chemical reaction by high-pressure hydrogen gas. Step 3: Liquid phase impregnation. Add the filling liquid under vacuum, remove the vacuum after adding, soak for more than 30 minutes, filter to remove the filling liquid, and vacuum dry to obtain boron-containing composite particles.

2. The method for preparing boron-containing composite particles according to claim 1, characterized in that, The specific steps of step 2 are as follows: Step 2.1: Ammonia washing. Place the boron-magnesium-aluminum composite particles prepared in step 1 into a rotary furnace, evacuate the gas through the gas port to remove gas, maintain the vacuum state, introduce ammonia, and then evacuate the vacuum again. Repeat this process more than 3 times. Step 2.2: Introduce high-pressure ammonia gas into the rotary furnace through the gas inlet, with a pressure of 0.2 MPa to 0.4 MPa. Start the vibration at a frequency of 10 Hz to 20 Hz. Simultaneously heat the furnace to a temperature of 40℃ to 50℃, and then maintain the pressure and temperature for vibration for more than 15 minutes. Step 2.3: Replace the ammonia in Step 2.1 with hydrogen and repeat the process multiple times. After multiple hydrogen washes, introduce high-pressure hydrogen into the rotary furnace. The pressure should not be lower than 1.0 MPa. Start the rotary furnace and heat it to 100℃~120℃. Then, maintain the pressure and temperature and rotate for more than 1 hour. Step 2.4: Remove hydrogen gas by depressurization to obtain solid hydrogen particles.

3. The method for preparing boron-containing composite particles according to claim 1, characterized in that, In step 3, the filling liquid includes perfluorohexane, vinylidene fluoride-trifluorochloroethylene copolymer and perfluorooctyl polyoxyethylene ether, wherein, by weight, there are 100 parts of perfluorohexane, 5 to 12 parts of vinylidene fluoride-trifluorochloroethylene copolymer and 0.5 to 2 parts of perfluorooctyl polyoxyethylene ether.

4. The method for preparing boron-containing composite particles according to claim 1, characterized in that, The rotary furnace includes a spherical pot (1), a plug (2), a heating jacket (3), and a vibration table (4). The heating jacket (3) is mounted on the vibration table (4). The interior of the heating jacket (3) is arc-shaped and has an opening on its side. A rotating shaft is located in the middle of the heating jacket (3), and the angle between the rotating shaft and the horizontal plane is 40° to 50°. The spherical pot (1) is located inside the heating jacket (3). A driving mechanism is located outside the rotating shaft. The driving mechanism is used to drive the spherical pot (1) to rotate around the rotating shaft. The vibration table (4) is used to drive the heating jacket (3) and the spherical pot (1) to rotate. The spherical pot (1) vibrates together. The heating jacket (3) is used to heat and keep the spherical pot (1) warm. The plug (2) is detachably installed at the opening of the spherical pot (1). The plug (2) is provided with a gas port (5) and a liquid port (6) that communicate with the spherical pot (1). The gas port (5) is used to introduce ammonia, hydrogen and to draw a vacuum. The liquid port (6) is used to inject filling liquid into the pot. The heating jacket (3) is provided with a water inlet (7) and a water outlet (8) for introducing hot water. The spherical pot (1) and the heating jacket (3) are connected by a ring track (9).

5. The method for preparing boron-containing composite particles according to claim 1, characterized in that, The boron in the boron-magnesium-aluminum composite particles in step 1 is amorphous boron.

6. A boron-containing composite particle, characterized in that, It is prepared by the method described in any one of claims 1 to 5.